El guaraní como fenómeno sociolingüístico transnacional: Actitudes y prácticas lingüísticas en las zonas fronterizas Paraguay-Argentina (Journal on studies and research of academic knowledge, 2014)
This research was carried out in the border territories of Paraguay and Argentina to understand and describe the reality of the Guarani language as a sociolinguistic transnational phenomenon, and thus contribute to a major understanding of international sociolinguistic scope of the Guarani language, the objective proposed to accomplish the goal were; identify attitudes toward the Guarani language; specify the attitudinal dimensions such as: linguistic pride, linguistic purism, linguistic insecurity and linguistic assessment; as well as to collect data on linguistic practices related to the Guaraní language in the border areas of Paraguay-Argentina.Through this research it was possible to detect that the linguistic reality of the population that makes up the Paraguay and Argentina border areas is no stranger to the quite widespread linguistic situation in the world population such as the use of a different language over the language considered most prestigious, therefore, the Guarani language is part of daily communication between people, where informants also demonstrated a positive attitude toward this language.
Keywords: attitude; sociolinguistics; linguistics; practice